Food Acceptance and Social Learning Opportunities in Semi‐Free Eastern Chimpanzees (Pan troglodytes schweinfurthii). (23rd December 2015) - Gustafsson, Erik; Saint Jalme, Michel; Kamoga, Dennis; Mugisha, Lawrence; Snounou, Georges; Bomsel, Marie‐Claude; Krief, Sabrina
Abstract: When confronted with novel foods, chimpanzees' responses combine a mixture of curiosity and cautiousness. Once the item is in the mouth, the initial cautiousness is followed by an aversion to bitter taste that is mediated mainly by the TAS2R gene family. For instance, variations on the TAS2R38 locus which has been studied extensively in humans have been associated with different acceptance of bitter substances. Surprisingly, while cautiousness and bitter taste aversion were selected to prevent any risk of poisoning, very few studies on novel food acceptance have included the vegetative parts of plants. Moreover, the studies were usually carried out with captive apes faced to a very restricted variety of non‐toxic plants, hardly making the results representative. This study aims to replicate previous findings obtained in zoos while controlling for these limitations. We provided nine subgroups of eastern chimpanzees ( Pan troglodytes schweinfurthii ) living in the Ugandan sanctuary of Ngamba Island with novel plants known to be consumed by wild chimpanzees of the same subspecies, as well as domestic plants, wild sapota fruit and grey clay used by human local communities. We also genotyped their TAS2R38 gene. Our results confirm the very low genetic heterogeneity for TAS2R38 in this chimpanzee subspecies. Chimpanzees were particularly cautious towards the vegetative parts of novel plants, likely reflecting their behavioural strategy for avoiding toxic compounds. We also confirmed their higher propensity towards testing sapota and clay, reflecting their ability to expand their diet. In contrast with the results found in zoos, familiar and novel less‐palatable vegetative parts of plants did not elicit many interindividual observations. This may be explained by the items presented, which could have been so novel to be considered as enrichment in captive conditions, where the apes are rarely exposed to plants.